EKSEKUSI TERHADAP ASET BANK ASING YANG BERADA DI LUAR NEGERI TERHADAP BANK ASING YANG TERLIKUIDASI DI INDONESIA - Dina Salsabila Heniasari; Lanni Agustin; Priskila Lambasa Septuagesima Siregar (Jurnal HUKUM BISNIS, 2019)
Not all customer deposits will be guaranteed by the Deposit Insurance Corporation, meaning that customer deposits are only guaranteed by the Deposit Insurance Corporation for Rp. 2,000,000,000.00 (two billion rupiah). The establishment of the Deposit Insurance Corporation must basically be able to protect customer funds. This research aims to determine the process of accountability of returning customer deposits of liquidated foreign banks in Indonesia and the execution of assets of foreign banks in the context of returning customer deposits in Indonesia. The research used is legal research that analyzes library research, by analyzing through legislation, literature, and other reference materials related to the regulation of Foreign Banks. The results of this research explain that. With the existence of the Deposit Insurance Agency, if the foreign bank is liquidated, the institution will replace customer deposits and complete the liquidation process. When the liquidation process of the assets of the foreign bank branch office is insufficient, bank assets abroad will be executed if the head office does not want to be responsible for the obligations of its branch office in Indonesia by completing it at the ICSID convention arbitration body (International Center for Settlement of Investment Disputes). Actually in taking assets abroad in the case of execution of assets that are overseas can be done if there are international agreements such as those carried out by the European Union by making an agreement on the European union convention on insolvency proccedings, this will facilitate the taking of assets in overseas